Theory-based evaluation of the implementation of energy efficiency policies for commercial buildings in China - Chmutina, Ksenia (2011)
This work investigates the current situation of energy efficiency policies for commercial buildings in China and evaluates their effectiveness using theory-based policy evaluation methodology. The thesis covers three main research areas: a discussion of energy efficiency improvement measures suitable for commercial buildings in the Chinese national context; a technical support for the theory-based policy evaluation presented in a form of four detailed case studies following the Design Standard for Energy Efficiency of Public Buildings GB20189-2005 (the Standard); and a discussion of the effectiveness of this Standard that was evaluated using theory-based policy evaluation. Future improvements for the energy efficiency in commercial building in China are suggested. Four case studies in different climate zones are used to examine the technical and economical effectiveness of the Design Standard for Energy Efficiency of Public Buildings GB20 189-2005, and investigate the main problems of buildings as energy consumers. The results show that the case study buildings have poor thermal insulation qualities as well as low energy efficiencies of lighting and equipment. The implementation of the Standard allows for the achievement of its individual targets aimed at the thermal insulation quality improvements as well as being cost effective. For a further energy consumption reduction, installation of renewable energy technologies is simulated, however it is limited by economic constraints. The theory-based policy evaluation shows that the Standard is an important tool in energy efficiency encouragement for commercial buildings in China. However, its effectiveness is negatively affected by a lack of monitoring system and a lack of awareness among the involved parties. Improvement of building energy efficiency is the quickest and the most effective way of creating energy savings in buildings. In order to make a better use of the Standard, the Chinese government should stimulate more interest among construction companies and building owners by creating carrot and stick policies.